2016
DOI: 10.1158/1940-6207.capr-15-0235
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Breast Density Reduction by Omega-3 Fatty Acids: Evidence from a Randomized Clinical Trial

Abstract: Preclinical data indicate that omega-3 fatty acids (n-3FA) potentiate the chemopreventive effect of the antiestrogen (AE) tamoxifen against mammary carcinogenesis. The role of n-3FA in breast cancer prevention in humans is controversial. Preclinical and epidemiologic data suggest that n-3FA may be preferentially protective in obese subjects. To directly test the protective effect of n-3FA against breast cancer, we conducted a 2-year, open-label randomized clinical trial in 266 healthy postmenopausal women (50%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…ω-3 PUFAs have recently been shown to ameliorate liver fibrosis by promoting YAP/TAZ degradation (14) and it is intriguing to speculate that beneficial effects of ω-3 PUFAs on breast cancers of obese individuals could be mediated via the inhibition of YAP/TAZ activity. This would be in keeping with results of a recent randomized clinical trial showing that ω-3 PUFAs decrease breast density in obese, but not overweight or normal weight postmenopausal women (15).…”
supporting
confidence: 85%
“…ω-3 PUFAs have recently been shown to ameliorate liver fibrosis by promoting YAP/TAZ degradation (14) and it is intriguing to speculate that beneficial effects of ω-3 PUFAs on breast cancers of obese individuals could be mediated via the inhibition of YAP/TAZ activity. This would be in keeping with results of a recent randomized clinical trial showing that ω-3 PUFAs decrease breast density in obese, but not overweight or normal weight postmenopausal women (15).…”
supporting
confidence: 85%
“…In preclinical studies, EPA appears to have higher proportional absorption into membranes of ER þ MCF-7 cells than DHA, whereas DHA may have greater proportional absorption in triple-negative cell lines and may be superior in reducing EGFR signaling due to better lipid raft absorption and spatial receptor disruption (8). Given the promising preclinical data in ER À cell lines and early reports that DHA may be superior to EPA in reducing inflammation, some early-phase breast cancer prevention studies, such as that reported in this issue, have used DHA alone, whereas others following more traditional epidemiologic leads have used combinations of EPA and DHA (9)(10)(11). A recently reported clinical trial in a relatively homogeneous cohort with abdominal obesity and baseline CRP evidence of inflammation found little difference in whole blood inflammatory gene expression between 2.7 g/day of EPA Figure 1.…”
Section: ó2018 Aacrmentioning
confidence: 99%
“…Patterson and collaborators did not associate EPA and DHA intake from fish oil supplements with breast cancer outcomes [ 230 ]. Sandhu et al found an increased effect of protective omega-3 fatty acid supplementation in higher body mass index women [ 244 ].…”
Section: Nutritional Supplementsmentioning
confidence: 99%